Periplasmic Proteins: Signalling, Kinetics, Thermodynamics and Expression: Exploring the properties and applications of periplasmic proteins (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Periplasmic proteins are an mportant class among the proteins. These proteins are important in signalling and transport of specific signals and the molecules. Hence, this property of periplasmic proteins can be exploited for the expression and the production of the different proteins. This review elaborates the extraction, binding, folding, signalling, role as transport proteins, kinetic and the thermodynamic properties of periplasmic proteins.